2008
DOI: 10.1111/j.1468-3083.2008.02713.x
|View full text |Cite
|
Sign up to set email alerts
|

Serologic markers of celiac disease in psoriatic patients

Abstract: Our results seem to imply an association between psoriasis and asymptomatic celiac disease/gluten intolerance. High percentage of positive results to guinea pig-derived tTG could be due to cellular activity of tissue transglutaminase in psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 43 publications
1
21
0
2
Order By: Relevance
“…Michaelsson et al (8) reported elevation in anti gliadin IgA, IgG, and tTG level in involved dermis than in non involved skin, which was significant (5.173.8% vs 0.770.5%, Po0.05) in 37 cases with psoriasis. Similar to our study Damasiewicz-Bodzek et al (20) have reported significantly higher level of serum anti tTG IgA and anti gliadin IgA levels in 67 psoriasis cases. Contrary to this, Kia et al (6) estimated IgA and IgG antibodies to gliadin in 100 cases of psoriasis, 100 cases of psoriatic arthritis, and 100 controls.…”
Section: Discussionsupporting
confidence: 93%
“…Michaelsson et al (8) reported elevation in anti gliadin IgA, IgG, and tTG level in involved dermis than in non involved skin, which was significant (5.173.8% vs 0.770.5%, Po0.05) in 37 cases with psoriasis. Similar to our study Damasiewicz-Bodzek et al (20) have reported significantly higher level of serum anti tTG IgA and anti gliadin IgA levels in 67 psoriasis cases. Contrary to this, Kia et al (6) estimated IgA and IgG antibodies to gliadin in 100 cases of psoriasis, 100 cases of psoriatic arthritis, and 100 controls.…”
Section: Discussionsupporting
confidence: 93%
“…U pacjentów z łuszczycą obserwuje się najczęściej współistnienie łuszczycowego zapalenia stawów, reumatoidalnego zapalenia stawów (RZS), nieswoistych zapaleń jelit [3], stwardnienia rozsianego, autoimmunologicznych chorób tarczycy [4] oraz celiakii [5][6][7][8]. Silniejszy niż w łuszczycy zwykłej związek z chorobami autoimmunologicznymi występuje w przypadku łuszczycowego zapalenia stawów [9,10].…”
Section: Wprowadzenieunclassified
“…In latent disease, serological markers are positive without enteropathy. In this case the enteropathy may occur later, and this should be taken into account in the future 1,21 The elevation of CRP and leukocytes could indicate inflammatory bowel disease. This needs to be interpreted with caution since these are nonspecific markers of intestinal inflammation and could be elevated due to another type of inflammation 22 .…”
Section: Discussionmentioning
confidence: 98%